Neurotrophic Factor-α1/Carboxypeptidase E Functions in Neuroprotection and Alleviates Depression - Xiao, Lan; Loh, Yoke Peng (Frontiers in Molecular Neuroscience, 2022)
Depression is a major psychiatric disease affecting all ages and is often co-morbid with neurodegeneration in the elderly. Depression and neurodegeneration are associated with decreased neurotrophic factors. In this mini-review the functions and potential therapeutic use of a newly discovered trophic factor, Neurotrophic factor-α1 (NF-α1), also known as Carboxypeptidase E (CPE), in depression and neuroprotection are discussed. NF-α1/CPE expression is enriched in CA3 neurons of the hippocampus. Families carrying null and homozygous non-sense mutations of the NF-α1/CPE gene share common clinical features including childhood onset obesity, type 2 diabetes, impaired intellectual abilities and hypogonadotrophic hypogonadism. Studies in animal models such as CPE knockout (KO) mice and CPEfat/fat mutant mice exhibit similar phenotypes. Analysis of CPE-KO mouse brain revealed that hippocampal CA3 was completely degenerated after weaning stress, along with deficits in hippocampal long-term potentiation. Carbamazepine effectively blocked weaning stress-induced hippocampal CA3 degeneration, suggesting the stress induced epileptic-like neuronal firing led to the degeneration. Analysis of possible mechanisms underlying NF-α1/CPE -mediated neuroprotection revealed that it interacts with the serotonin receptor, 5-HTR1E, and via β arrestin activation, subsequently upregulates ERK1/2 signaling and pro-survival protein, BCL2, levels. Furthermore, the NF-α1/CPE promoter contains a peroxisome proliferator-activated receptor (PPAR) binding site which can be activated by rosiglitazone, a PPAR agonist, to up-regulate expression of NF-α1/CPE and neurogenesis, resulting in anti-depression in animal models. Rosiglitazone, an anti-diabetic drug administered to diabetic patients resulted in decline of depression. Thus, NF-α1/CPE is a potential therapeutic agent or drug target for treating depression and neurodegenerative disorders.